Cellular and humoral immunity in a wild mammal: Variation with age & sex and association with overwinter survival. Issue 24 (15th November 2016) - Watson, Rebecca L.; McNeilly, Tom N.; Watt, Kathryn A.; Pemberton, Josephine M.; Pilkington, Jill G.; Waterfall, Martin; Hopper, Phoebe R.T.; Cooney, Daniel; Zamoyska, Rose; Nussey, Daniel H.
Abstract: Immune defenses are expected to be crucial for survival under the considerable parasite pressures experienced by wild animals. However, our understanding of the association between immunity and fitness in nature remains limited due to both the complexity of the vertebrate immune system and the often‐limited availability of immune reagents in nonmodel organisms. Here, we use methods and reagents developed by veterinary researchers for domestic ungulates on blood samples collected from a wild Soay sheep population, to evaluate an unusually broad panel of immune parameters. Our evaluation included different innate and acquired immune cell types as well as nematode parasite‐specific antibodies of different isotypes. We test how these markers correlate with one another, how they vary with age‐group and sex, and, crucially, whether they predict overwinter survival either within or among demographic groups. We found anticipated patterns of variation in markers with age, associated with immune development, and once these age trends were accounted for, correlations among our 11 immune markers were generally weak. We found that females had higher proportions of naïve T cells and gamma–delta T cells than males, independent of age, while our other markers did not differ between sexes. Only one of our 11 markers predicted overwinter survival: sheep with higher plasma levels of anti‐nematode IgG antibodies were significantly more likely to survive the subsequent high mortality winter, independent of age, sex, or weight. This supports a previous finding from this study system using a different set of samples and shows that circulating antibody levels against ecologically relevant parasites in natural systems represent an important parameter of immune function and may be under strong natural selection. Our data provide rare insights into patterns of variation among age‐ and sex groups in different T‐cell subsets and antibody levels in the wild, and suggest that certain types of immune response—notably those likely to be repeatable within individuals and linked to resistance to ecologically relevant parasites—may be most informative for research into the links between immunity and fitness under natural conditions. Abstract : Immune defenses are expected to be crucial for survival; however, our understanding of the association between immunity and fitness in nature remains limited. We use blood samples, collected from a wild Soay sheep population, to evaluate an unusually broad panel of immune parameters, including innate and acquired immune cell types as well as nematode parasite‐specific antibodies. We test how these markers correlate with one another, how they vary with age group and sex, and, crucially, whether they predict overwinter survival.